INTERJECTION IN VERNACULAR: THE TYPES OF INTERJECTION ON SOCIETY OF KALIWATUKRANGGAN, PURWOREJO REGENCY, CENTRAL JAVA - Wulandari, Suci Mustika; Afdaleni, Afdaleni; Sari, Nofrika (Lexeme : Journal of Linguistics and Applied Linguistics, 2022)
Abstract The object of this research is interjections that appear in daily life of Kaliwatukranggan people, Purworejo regency. The aim of this research is (1) to describe the types of interjection in Kaliwatukranggan; (2) to identify feelings, which are involving in it. The result of this study showed that (1) 11 types of interjection are found in Kaliwatukranggan, Purworejo regency There are 3 types of interjections which is categorized lexically and semantically, that is, primary interjection and secondary interjection. Furthermore, 17 interjections are categorized into specific feeling which consist of two sub-types; there are interjections (response cries) that do not involve others and interjections (response cries) that involve others. (2) found 9 types of feelings that Goffman theory purposed. In this case, researcher also found new feelings: mad, wonder, and disappointment.Keyword: Interjection, Vernacular, Kaliwatukranggan.